Correlation of neurological level and sweating level of injury in persons with spinal cord injury. (2nd November 2021) - Trbovich, Michelle; Ford, Ashley; Wu, Yubo; Koek, Wouter; Wecht, Jill; Kellogg, Dean
Abstract : Objective: Thermoregulatory dysfunction after spinal cord injury (SCI) impairs quality of life and predisposes persons to life-threatening sequela of heat-related illness (HRI) in conditions of high ambient temperature. SCI clinicians currently have no objective way to predict which persons are at greatest risk of HRI. Evaporative cooling via sweating is the body's most efficient mechanism of heat dissipation. The relationship between the neurological level of injury (NLOI) and the degree of sudomotor dysfunction is not well defined. This study examines the relationship between the NLOI and sweating level of injury (SwLOI). This information can assist SCI clinicians in identifying individuals with SCI who have most impaired sudomotor function and thus highest risk of HRI. Design: Observational. Setting: Human physiology laboratory. Participants: 10 persons with tetraplegia (TP), 14 with paraplegia (PP) and 10 able-bodied (AB). Intervention: Passive heat stress (1°C rise in core temperature) with sweat responses (SR) quantified with the starch iodine test. Outcome measures: The most caudal dermatomal level in which sweating was visualized was recorded as the SwLOI, which was compared to the NLOI. Minimum, maximum and median differences between NLOI and SwLOI were calculated. Results: Persons with tetraplegia demonstrated no SR. Persons with paraplegia demonstrated SR at a median of 1 level below NLOI. Able-bodied controls demonstrated sweating on all skin surface areas. Conclusions: Persons with motor complete tetraplegia lack evaporative cooling capacity through SR during passive heat stress predisposing them to HRI. Meanwhile, persons with paraplegia sweat on average 1 dermatomal level below their NLOI.